“Kurd and BarsisiAbid” - د. مزگین عەبدورەحمان ئەحمەد (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research is entitled “Kurd and BarsisiAbid” which is adopted from the story of a famous Kurdish poet named “ FaghiTayran”. This story describes a religious person that after 70 years of spiritual live was deceived by Satan and lost all his good faith and spiritual life in a very short time. He couldn’t protect and preserve himself from the whispers of Satan. This story consists of 211 couplets and it represents a wonderful image of unconsciousness of human beings when they totally depend on such kind of evil people who always deceived them. In some cases, when innocent people face difficulties and problems in their daily life and they ask for help from devils, in contrast, they cannot get enough support from them. The researcher intended to describe and illustrate the similarities between the age of “BarsisAbid” and Kurd’s current situation applying descriptive analyzing method, since Kurdish community is experiencing the same conditions as Abid’s age. This research consists of two parts: First part: presents the literary work of the poet’s story and a short description of his life, as well as, a short description of the poetry. Second part: presents a study on the poet’s perception towards Kurdish current situation in terms of psychological, political, and social conditions. Finally, the result of this study has been illustrated and analyzed in some sections, and this research ends with a list of references.